Ischemic Stroke in Children and Young Adults With Congenital Heart Disease. Issue 2 (February 2016) - Mandalenakis, Zacharias; Rosengren, Annika; Lappas, Georgios; Eriksson, Peter; Hansson, Per‐Olof; Dellborg, Mikael
Abstract : Background: Patients with congenital heart disease (CHD) may be at increased risk of ischemic stroke due to residual shunts, arrhythmias, and other cardiovascular abnormalities. We studied the relative risk and potential factors for developing ischemic stroke in children and young adults with CHD in Sweden. Methods and Results: All patients in the Swedish Patient Register with a diagnosis of CHD, born between 1970 and 1993, were identified and compared with 10 controls for each patient, matched for age, sex, and county and randomly selected from the general population. Follow‐up data through 2011 were collected for both groups. Of 25 985 children and young adults with CHD (51.5% male, 48.5% female), 140 (0.5%) developed ischemic stroke. The hazard ratio for CHD patients developing ischemic stroke was 10.8 (95% CI, 8.5–13.6) versus controls. All major Marelli groups had significantly increased risk, but because of small CHD‐group sizes, only atrial septal defect/patent foramen ovale, double‐inlet ventricle, and aortic coarctation displayed significantly increased risk. In multivariate analysis of CHD patients, congestive heart failure carried the highest risk for developing ischemic stroke (hazard ratio 6.9 [95% CI, 4.7–10.3]), followed by hypertension and atrial fibrillation, which were also significantly associated with increased risk of ischemic stroke. Conclusions: The risk of developing ischemic stroke was almost 11 times higher in young patients with CHD than in the general population, although absolute risk is low. Cardiovascular comorbidities were strongly associated with the development of ischemic stroke in young CHD patients.